2020
DOI: 10.1016/j.virusres.2020.198021
|View full text |Cite
|
Sign up to set email alerts
|

On the interactions of the receptor-binding domain of SARS-CoV-1 and SARS-CoV-2 spike proteins with monoclonal antibodies and the receptor ACE2

Abstract: A new betacoronavirus named SARS-CoV-2 has emerged as a new threat to global health and economy. A promising target for both diagnosis and therapeutics treatments of the new disease named COVID-19 is the coronavirus (CoV) spike (S) glycoprotein. By constant-pH Monte Carlo simulations and the PROCEEDpKa method, we have mapped the electrostatic epitopes for four monoclonal antibodies and the angiotensin-converting enzyme 2 (ACE2) on both SARS-CoV-1 and the new SARS-CoV-2 S receptor binding domain (RBD) proteins.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(132 citation statements)
references
References 83 publications
(161 reference statements)
6
125
0
1
Order By: Relevance
“…We focused in the S 461–493 sequence; whose immunogenicity was first validated in sheep given the lack of experimental validation of protective epitopes from the S protein. This selection was guided by the in silico prediction of B cell epitopes and by the fact that receptor binding domain (RBD) is recognized as a target of neutralizing antibodies in the case of SARS-CoV-1 [ 41 , 42 ]. The selected S 461–493 peptide induced high levels of IgG (titers up to 60,000) under an immunization scheme of three months comprising the use of a strong adjuvant; confirming that S 461–493 carries a B cell epitope.…”
Section: Discussionmentioning
confidence: 99%
“…We focused in the S 461–493 sequence; whose immunogenicity was first validated in sheep given the lack of experimental validation of protective epitopes from the S protein. This selection was guided by the in silico prediction of B cell epitopes and by the fact that receptor binding domain (RBD) is recognized as a target of neutralizing antibodies in the case of SARS-CoV-1 [ 41 , 42 ]. The selected S 461–493 peptide induced high levels of IgG (titers up to 60,000) under an immunization scheme of three months comprising the use of a strong adjuvant; confirming that S 461–493 carries a B cell epitope.…”
Section: Discussionmentioning
confidence: 99%
“…Both have similar diameters, with the size of SARS-CoV-2 being 65–125 nm, and the size of SARS-CoV being 80–120 nm ( Shereen et al, 2020 ). The host cell receptors of both SARS-CoV-2 and SARS-CoV are the ACE-2 protein, but the affinity between SARS-CoV-2 and receptor protein is higher which would facilitate a relatively fast transmission of corresponding diseases ( Giron et al, 2020 ). Van et al (2020) have established an experimental environment to test the stability of SARS-CoV-2 and SARS-CoV, and they have found that the survival time (aerosol half-life) of the two viruses in the air after artificial aerosolizing was similar, but the retention time of SARS-CoV-2 on the surfaces of objects was relatively longer, which increased the risk of resuspension.…”
Section: Influence Of Human-exhaled Aerosol On the Transmission Of Comentioning
confidence: 99%
“…The existence of the furin mechanism overcomes the "default" state (mostly in the "down" conformation) of the SARS-CoV-2 spike RBD, which is inefficient for host cell binding. The affinity of ACE2 for the SARS-CoV-2 S1 spike protein RBD has recently been reported to be similar (Wells 2020;Correa Giron et al 2020) or 10-20 times higher than that of SARS-CoV (Wrapp et al 2020). In silico modelling of the SARS-CoV-2 protease involved in virion entry into cells has disclosed a high degree of flexibility of the protein, which not only involves the site where a known inhibitor binds, but also exposes other putative sites where enzyme blockers could bind (Wells 2020).…”
Section: Structures Of Cov Surface Spike Protein S and Host Cell Recementioning
confidence: 99%